2019
DOI: 10.3389/fphys.2019.00577
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human CRY1 and CRY2 Knockout Cells Using Duplex CRISPR/Cas9 Technology

Abstract: Circadian clocks are endogenous oscillators essential for orchestrating daily rhythms in physiology, metabolism and behavior. While mouse models have been instrumental to elucidate the molecular mechanism of circadian rhythm generation, our knowledge about the molecular makeup of circadian oscillators in humans is still limited. Here, we used duplex CRISPR/Cas9 technology to generate three cellular models for studying human circadian clocks: CRY1 knockout cells, CRY2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…S2E). Knocking out the CRY1 in this cell line resulted in a shorter period compared to wild-type controls as in agreement with previously published data 27 . Notably, when U2OS CRY1 -/-Bmal1-dLuc cells were treated with the M47, no change was observed in the period length of the circadian rhythm (Fig.…”
Section: Characterization Of M47supporting
confidence: 93%
“…S2E). Knocking out the CRY1 in this cell line resulted in a shorter period compared to wild-type controls as in agreement with previously published data 27 . Notably, when U2OS CRY1 -/-Bmal1-dLuc cells were treated with the M47, no change was observed in the period length of the circadian rhythm (Fig.…”
Section: Characterization Of M47supporting
confidence: 93%
“…The resulting fluorescent knock-in cell lines enabled us to visualize endogenously expressed PER2 and CRY1 proteins -two canonical circadian repressors -for the first time in single human live cells. We are confident that the fusion proteins are functional, because cells with a bi-allelic knock-in of PER2or CRY1-fusion proteins display normal circadian rhythms, in contrast to Per2 or Cry1 knockout cells which are hardly rhythmic (34,35). This is further supported by reports that homozygous Per2-Venus and Per2-Luc knock-in mice display normal circadian rhythms, and rhythmically expressed CRY1-EGFP can rescue rhythmic behavior in otherwise arrhythmic Cry1/2 double knock-out mice (16,36).…”
Section: Discussionmentioning
confidence: 97%
“…In doing so, they transfected U2-OS cells stably expressing a Bmal1-Luciferase reporter with a lentivirus expressing Cas9 and two sgRNA targeting different sites in the www.nature.com/scientificreports/ Fbxl3 gene and reported that CRISPR-Cas9-based Fbxl3 KO dampened Bmal1 promoter-driven luminescence oscillation. The same group then utilized a CRISPR-Cas9 system to generate CRY1 and CRY2 double KO cells 36 . Furthermore, Clock targeting has been efficient in mouse embryonic stem cells when investigating the non-clock functions of the Clock gene 25 , while Lee and colleagues expanded the repertoire of direct CRISPR-Cas9 targets by designing an adenoviral vector system for efficiently generating null mutant cell lines 28 .…”
Section: Discussionmentioning
confidence: 99%